2016
DOI: 10.1161/circheartfailure.115.002562
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Myocardial Flow in Heart Failure Patients With Preserved Ejection Fraction

Abstract: Background— There remains limited insight into the pathophysiology and therapeutic advances directed at improving prognosis for patients with heart failure with preserved ejection fraction (HFpEF). Recent studies have suggested a role for coronary microvascular dysfunction in HFpEF. Rb-82 cardiac positron emission tomography imaging is a noninvasive, quantitative approach to measuring myocardial flow reserve (MFR), a surrogate marker for coronary vascular health. The aim of this study was to determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
79
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(85 citation statements)
references
References 36 publications
5
79
0
1
Order By: Relevance
“…26 Finally, recent studies have shown impairment in coronary microvascular structure and function that are related in large part to abnormalities in NO-cGMP bioavailability in HFpEF, which may limit O 2 delivery and utilization in the heart as well as the periphery. 27-29 …”
Section: Pathophysiology Of Hfpefmentioning
confidence: 99%
“…26 Finally, recent studies have shown impairment in coronary microvascular structure and function that are related in large part to abnormalities in NO-cGMP bioavailability in HFpEF, which may limit O 2 delivery and utilization in the heart as well as the periphery. 27-29 …”
Section: Pathophysiology Of Hfpefmentioning
confidence: 99%
“…5 Over 1000 PET-referred patients had a normal ejection fraction and no PET-evidence of epicardial coronary artery disease. Of these, 78 were retrospectively identified to have a previous diagnosis of HFpEF by chart review and were compared to 112 normotensive and 186 hypertensive controls.…”
Section: Coronary Microvascular Dysfunction and Hfpefmentioning
confidence: 99%
“…The potential impact of diffuse microvascular endothelial inflammation on the functional and structural integrity of the microcirculation and the role that microcirculatory dysfunction itself may play in HFpEF pathophysiology are unclear. In this issue of Circulation Heart Failure , Srivaratharajah et al 5 add to a small but growing body of literature suggesting a role for microvascular dysfunction in the pathophysiology of HFpEF.…”
mentioning
confidence: 99%
“…This model has been shown to display several features of human HFpEF, including elevation in LVEDP, hypertension, oxidative stress, and coronary microvascular dysfunction. 1820, 2629 However, we did not perform experiments to demonstrate that these animals had diastolic dysfunction or true clinical heart failure, and further study is warranted in this regard.…”
Section: Discussionmentioning
confidence: 96%